PENYULUHAN WAR ON DRUGS DAN REACHING OUT REMAJA ANTI NARKOTIKA (DISELENGGARAKAN DI BADAN NARKOTIKA NASIONAL KABUPATEN PELALAWAN): (Diselenggarakan di Badan Narkotika Nasional Kabupaten Pelalawan) - Tutrianto, Rio; Rinaldi, Kasmanto (Komunitas Manajemen Kompetitif, 2023)
Adolescence is a very exciting time for most people. In this phase, they begin to meet a wider social environment, adapt, play and learn together, accompanied by well-developed logical abilities. Even teenagers are often referred to as agents of change or agents of change. To become a quality generation, adolescents must be able to avoid and overcome quite complex adolescent problems along with their transition period. Adolescence is a phase of identity crisis or the search for self-identity. The characteristics of adolescents who are in the process of seeking self-identity often cause problems for adolescents, one of which is drugs. The purpose of anti-narcotics youth counseling through youth interactive dialogue is to provide understanding and develop applicable abilities to adolescents in creating adaptive friendships in rejecting drug abuse. The benefit of carrying out Anti-Narcotics Adolescent counseling through interactive youth dialogue is that the youth who are trained have the readiness to be clean from drugs, foster social confidence so that it will strengthen the positive image of adolescents. It is hoped that the outputs and achievement targets of the Counseling on War On Drugs and Reaching Out Youth Against Narcotics are expected to be contained in academic publications and printed media on a local and national scale.